Arthroscopic capsular repair using proximal advancement for instability following hip arthroscopic surgery: a case report. Issue 1 (25th February 2019) - Nishikino, Shoichi; Hoshino, Hironobu; Hotta, Kensuke; Furuhashi, Hiroki; Koyama, Hiroshi; Matsuyama, Yukihiro
Abstract: Arthroscopic capsular reconstruction has been reported for joint capsule tear and joint instability after hip arthroscopic surgery. However, the procedure is complicated and requires proficiency. Herein, we present a case of mild dysplasia and instability following arthroscopic surgery performed against pain due to synovitis and labral injury. The patient refused osteotomy of the hip joint, so we performed hip arthroscopic surgery using a new method of arthroscopic capsular repair using proximal advancement. A 37-year-old woman underwent hip arthroscopic surgery two times at the right side and periacetabular osteotomy at the left side. She noticed instability of the right hip joint after the second hip arthroscopic surgery. For the joint capsular management at the second surgery, which was not suitable for capsular plication, arthroscopic capsular repair using proximal advancement was performed by lifting the distal capsule to the acetabular margin. This method is less technically demanding compared with capsular reconstruction, and it can securely achieve joint stability by retensioning the joint capsule and iliofemoral ligament. Patient-reported outcomes were assessed by modified Harris hip score (mHHS), non-arthritic hip score (NAHS) and visual analog scale (VAS). The patient reported an increase in the mHHS from 35.2 pre-operatively to 90.1, the NAHS increased from 50 pre-operatively to 88.7, and the VAS score improved from 9 points pre-operatively to 1 point at 2 years post-operatively. To our knowledge, this is the first report on arthroscopic capsular repair using proximal advancement in a patient with hip instability following hip arthroscopic surgery.